A Novel Surgical Approach to Treat Lymphangioma of the Breast and Prevent Seroma - Islam Ud Din Iftikhar, Farah Kanwal, Iqra Tahir, Faisal Riaz, Javeria Rafique, Muhammad Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Lymphangioma of the breast is a rare benign lymphatic malformation that often necessitates surgical excision due to cosmetic concerns or progressive enlargement. Objective: To evaluate the effectiveness of a novel surgical technique incorporating en bloc excision, targeted lymphatic ligation, and fibrin sealant application in minimizing postoperative seroma formation following breast lymphangioma surgery. Methods: A prospective interventional study was conducted at Cancer Care Hospital and Research Center (CCH & RC) over a period of 6 Months from 1st March 2023 to 30th August 2023 involving 85 patients with clinically or radiologically confirmed breast lymphangioma, selected through non-probability consecutive sampling. Data on demographics, lesion characteristics, operative duration, drain duration, and postoperative complications were collected. Seroma formation, defined as clinically evident fluid collection requiring aspiration or causing wound dehiscence, was the primary outcome. Results: Out of 85 patients undergoing the novel surgical approach for breast lymphangioma, the mean age was 36.4 years, and average lesion size was 5.3 cm. The seroma rate was 7.1% (6 patients), markedly lower than the 28.2% seen in historical controls (p < 0.01). The average operative time was 58.2 minutes, and mean drain duration was 2.8 days. Only 3.5% experienced minor wound infections, and no readmissions occurred. Overall, the technique was associated with favorable clinical and cosmetic outcomes, minimal complications, and reduced postoperative morbidity. Conclusion: The novel surgical technique demonstrated a significant reduction in postoperative seroma rates among patients with breast lymphangioma. Incorporating targeted lymphatic ligation and dead-space obliteration appears to be an effective strategy for optimizing surgical outcomes in this rare condition. Keywords: Lymphangioma, breast surgery, seroma prevention, lymphatic malformation, fibrin sealant, surgical technique.